The value of liver scanning in pediatric age group with special emphasis on histopathological correlation - Erbengi, Günaydın (The Turkish Journal of Pediatrics, 1975)
Liver scintigraphy is one of the most practical and appropriate diagnostic tests in shedding light to the liver disorders. A liver scintigraphy is imperative to differentiate space-occupying lesions, from non-space-occupying lesions of the liver and neighbouring organs. It is very useful for follow-up studies of the cases who had had operations and chemotherapy.